The Problem of Explaining the Brain-Consciousness Relationship and the Function of the Brain in Henri Bergson's Philosophy of Mind - Çelebi, Vedat (Fırat University, 2025)
This article examines fundamental concepts including consciousness, memory, and the brain, which are central to Bergson’s philosophy of mind, in relation to one another. Specifically, it focuses on the problem of whether consciousness can be explained independently of the body or brain. Bergson exhibits a distinct perspective from classical Cartesian dualism, which is one of the basic approaches of philosophy of mind. Bergson does not provide a comprehensive explanation of the soul or consciousness that is entirely independent of the body or brain and considered eternal in a substantial sense. Bergson evaluates the relationship between consciousness and the brain not as two distinct substances and qualities, but in terms of their functional interdependence in a non-reductionist manner, focusing on the concept of memory. Therefore, since Bergson rejects the notion that consciousness and brain, and memory and matter are identical or innate as two distinct substances, demonstrating a different perspective from both materialism and parallelism and the substance dualism found in Cartesian philosophy. In this context, this article examines the relationship between consciousness, brain, and memory in the context of the problem of reduction and the criticism of parallelism, materialism, and dualism. In conclusion, this article aims to examine Bergson’s philosophy of mind through questions such as, Are consciousness, the brain, and memory identical? Are consciousness and the brain two distinct substances? Is consciousness a function of the brain? What is the function of the brain? Can consciousness be reduced to the brain?

Makalede, Bergson’un zihin felsefesinin merkezinde olan bilinç, hafıza ve beyin gibi temel kavramları birbiriyle ilişkili olarak irdelenmektedir. Özellikle de bilincin, beden ya da beyinden bağımsız olarak açıklanmasının mümkün olup olmadığı problemine odaklanılmaktadır. Bu noktada, Bergson’un zihin felsefesinin temel yaklaşımlarından biri olan klasik Kartezyen düalizminden farklı bir tavır sergilediğini belirtmemiz gerekir. Bergson’da, beden ya da beyinden tamamen bağımsız ve ezeli olarak kabul edilen tözsel anlamda bir ruh ya da bilinç açıklaması söz konusu değildir. Bergson, bilinç ve beyin arasındaki ilişkiyi iki ayrı töz ve nitelikleri açısından değil de işlevleri ve dayanışma ilişkisi bağlamında değerlendirmekte ve hafıza kavramını merkeze alarak indirgemeci olmayan bir tavırla açıklamaktadır. Dolayısıyla Bergson, bilinç ve beyin ile hafıza ve maddeyi özdeş ya da doğuştan gelen iki ayrı töz olarak kabul etmediği için hem materyalizm ve paralelizmden hem de Kartezyen felsefede karşımıza çıkan töz (cevher) düalizminden farklı bir tavır sergiler. Bu çerçevede makalede; bilinç, beyin ve hafıza ilişkisi indirgeme problemi ve paralelizm, materyalizm ve düalizm eleştirisi bağlamında irdelenmeye çalışılacaktır. Sonuç olarak, makalenin amacı; Bilinç, beyin ve hafıza özdeş midir? Bilinç ve beyin iki ayrı töz müdür? Bilinç, beynin işlevi midir? Beynin işlevi nedir? Bilinç, beyne indirgenebilir mi? gibi sorular üzerinden Bergson’un zihin felsefesini değerlendirmektir.
Henri Bergson’un Zihin Felsefesinde Beyin-Bilinç İlişkisinin Açıklanması Problemi ve Beynin İşlevi
Keywords: Contemporary Philosophy; Çağdaş Felsefe